Efektifitas Penerapan Model Project Based Learning Terhadap Kemampuan Berpikir Kreatif Siswa Kelas V SDN 137 Palembang - Hermita, Noren; Ramadhani, Erfan; Fakhrudin, Ali (ANTHOR: Education and Learning Journal, 2023)
This study aims to determine the effectiveness of the application of the project based learning model on the creative thinking skills of fifth grade students at SD Negeri 137 Palembang. The research method used in this study was an experiment with a sample of 42 people. The sample in this study was taken using a total sampling technique. The data collection technique used was a test in the form of an essay totaling 5 questions. Based on the results of the study it can be seen that the significance value of 0 = 0.003 issmaller than alpha (α) = 0.05; with a tcount value of 3.226 and a ttable value of 1.672. It turns out that tcount > ttable or 2.500 > 1.672. This means that the use of the project based learning model has effectiveness on the creative thinking skills of fifth grade students at SD Negeri 137 Palembang in learning science.